ENHANCING ORAL SPEECH COMPETENCIES: A COMPREHENSIVE APPROACH TO STUDENT DEVELOPMENT - Gofurova Gulhayo Bakhtiyorjon qizi (Scholar Express Journal, 2023)
This article explores various methodologies for enhancing oral speech competencies among students. It delves into the importance of a supportive learning environment, vocabulary enrichment, technology integration, peer interactions, creative expression, cultural awareness, real-world applications, and fostering self-reflection. The comprehensive strategies discussed aim to empower students with effective communication skills, nurturing their confidence, creativity, and critical thinking abilities
Keywords: Oral speech competencies; Communication skills; Pedagogy